Optimization of the Cage Environment To Improve Broiler Health - Retno Widyani; Bayu Arisandi; Maulana Akbar (Jurnal Agrosci, 2026)
Background. Pen environment management is a key factor in maintaining broiler health and performance, especially in closed house systems. Aims. This study aims to describe the application of cage environment optimization to the health and productivity of broiler chickens in the Cucu Nurlela Farm Cage as a partner of PT ASPM Paranjê in Majalengka Regency, West Java. Method. The method used is descriptive research with a participatory observational approach through Field Work Practice (PKL) activities, which involves direct observation and active involvement in the entire broiler chicken rearing cycle. The aspects observed included temperature and humidity regulation, ventilation management, ammonia control, litter management, biosecurity implementation, chicken health management, and production success indicators. The observation results show that the cage temperature and humidity are within the optimal range for the chickens' age, with a relative humidity of 50–70% and effective ventilation to suppress ammonia accumulation. Results. Implementing zoning-based biosecurity, daily health observations, isolating sick chickens, and providing vitamins, medicines, and herbal remedies can help maintain the flock's overall health. Production performance indicators show a mortality rate of 2.78% and a Feed Conversion Ratio (FCR) of 1.47, reflecting feed efficiency and successful cage management. Conclusion. Optimizing the cage environment in the closed-house system plays a significant role in maintaining broiler chicken health, reducing mortality, and increasing production efficiency.